Innovative development of the national economy in the context of global economic trends (Economics and region, 2025)
The article explores the theoretical and methodological foundations of the innovative development of the national economy in the context of ongoing global transformations. The study focuses on identifying and systematizing the key global trends that generate increasing innovation pressure on transitional economies. These trends include the growing role of high-tech exports, the globalization of knowledge and capital markets, digital transformation, the tightening of environmental standards, and the fragmentation of global value chains. The authors emphasize that such challenges require the implementation of a complex, multisectoral policy approach aimed at enhancing long-term competitiveness and technological sovereignty. Based on current statistical data and recent scientific publications, the paper highlights that Ukraine’s innovation activity remains critically low, primarily due to institutional instability, weak support for research and development (R&D), underdeveloped mechanisms for technology transfer, and insufficient integration into global innovation systems. The lack of systemic coordination between stakeholders—public authorities, the private sector, and scientific institutions—has been identified as a key constraint on the effectiveness of national innovation policy. The article proposes a set of strategic policy directions that are essential for unlocking Ukraine’s innovation potential. These include the formation of network-based scientific-industrial clusters, the development of public-private partnerships in the R&D sector, the digitalization of public innovation management processes, and the support of export-oriented innovation projects. Special attention is given to the importance of harmonizing Ukraine’s regulatory and institutional frameworks with international standards and global innovation practices. The study concludes that the transformation of the institutional environment is a necessary precondition for building an effective national innovation system capable of ensuring technological modernization and sustainable economic development.
Keywords: innovation development; global transformations; innovation policy; digitalization; public-private partnership; clustering; technology transfer; competitiveness